Effect of Firring Heating Rate on the Density, Porosity, Vickers Hardness and Microstructure of the Crucible Specimens - Rusiyanto, R.; Meiartha, REGA; Fitriyana, Deni Fajar; Sudiyono, S.; setiadi, rizki; Siregar, Januar Parlaungan; Ansori, CHUSNI (JURNAL ILMIAH MOMENTUM, 2024)
Failure in the results of making the crucible is cracking and even deformation. Cracks that occur can cause fluid leakage when melting so that it disrupts the casting process. The quality of the crucible can be influenced by factors including the selection of constituent materials, particle size, the amount of pressure, and the length of the firring process of heat treatment and cooling in the furnace. This study aims to determine the effect of heating rate on crucible made from clay and kaolin and molasses as a binder. With the treatment of different heating rates in the firring process, namely 3 ℃ / min, 4 ℃ / min, 5 ℃ / min, 6 ℃ / min, and 7 ℃ / min.  The composition of the materials used is 40% clay, 40% kaolin, and 5% molasses and 15% water as the total mass. The process of making specimens begins with crushing clay, sieving clay 100 mesh. Mixing process using twin screw extruder machine repeatedly for 45 minutes. Molded cylindrical size 20 x 20 mm, free air drying for 8 days, firring process at 1000 ℃ holding time 1 hour. The results showed that the difference in heating rate did not affect the change in chemical elements but the best heating rate was at 3℃/min showing a denser morphology, density value of 1.62 g/cm3, porosity value of 23%, and Vickers hardness value of 20.43 HVN.